Kajian in Silico Aktivitas Antioksidan Senyawa Bioaktif dalam Minyak Serai (Cymbopogon citratus) - Sari, Dewi Ratih Tirto; Bare, Yohanes (Al-Kimia, 2021)
stress oxidative is a factor promoting metabolic syndrome and other diseases. oxidative stress could be minimalized by exogen and endogen antioxidants. Essential oil from Cymbopogon citratus extract have potential activities as anti-inflammatory and relaxing. This study determined the potential activity as antioxidant through kelch ECH associating protein 1 (KEAP1) inhibition. Four phytosterol compounds from Cymbopogon citratus essential oil, including 3,7-dimethyl-1,3,6-octatriene, decanal, elemol, dan selina- 6-en-4-ol, were downloaded from PubChem database. four compounds were docked with KEAP1 protein and analyzed using Discovery studio ver. 19.0.0. 3,7-dimethyl-1,3,6-octatriene, decanal, elemol, and selina-6-en-4-ol bound to KEAP1 in certain amino acid residues with hydrophobic interaction and hydrogen bond. Interestingly, 3,7-dimethyl-1,3,6-octatriene proved five hydrophobic interaction, higher than decanal and selina-6-en-4-ol. The elemol, and selina-6-en-4-ol interacted with KEAP1 showing lower binding affinity and tight interaction. This study suggested that 3,7-dimethyl-1,3,6-octatriene, decanal, elemol, and selina-6-en-4-ol promoted antioxidant activity.